Influencia de las herramientas tecnológicas en el proceso de aprendizaje remoto y la retroalimentación para los niños de primero y segundo grado de primaria - Hurtado Barrera, Silvino (2021)
The research called "Influence of technological tools in the remote learning process and feedback for children in the first and second grade of primary school", was carried out with the boys and girls of the first and second grades of the educational institution N ° 0599 “Micaela Seminario de Romero” from the district of Santa Lucía, province of Tocache and the San Martín region, in order to find viable alternatives to develop learning activities remotely through the use of ICT so that children have the participation active with his classmates and his teacher, without having to miss face-to-face classes. At present, technological resources become more important in the learning process, for the same reason that they are generators of self-learning and the consolidation of the autonomy of first and second year students. Students find more meaning when they learn interactively, when they develop collaborative learning activities through the use of educational software and technological devices such as the computer, tablet, laptop, and even XO laptops in the case of my children and girls. During the remote education that began in April 2020, I have implemented together with the parents of my section various technological tools such as Kahoot, eXelearnig, Hot Potatoes, Jclic, Ardora; With these tools we have awakened the common interest of students to be interactive, creative and motivated to learn by doing and creating their own content. The use of ICTs in times of the pandemic turns out to be of vital importance to provide the continuity of the educational service throughout our country. These same technological resources are used to provide feedback to students in order to raise the quality of learning. For learning to be meaningful, feedback must be through reflection and discovery.